Graphic creativity assessment: Psychometric properties in college students from Buenos Aires - Freiberg Hoffmann, Agustín (2017)
Research on creativity has acquired major development due to its relevance concerning teaching in college. Its assessment is generally conducted by means of verbal and graphic measures. A short scale to measure verbal creativity (CREA) in college students from Buenos Aires is currently available. However, right now there are no similar scales designed to assess graphic creativity. In view of that, this study will analyse psychometric features of the ECG scale locally known as Evaluación de la Creatividad Gráfica – Graphic Creativity Assessment, to be employed in the academic milieu in order to provide a complementary measure of verbal creativity. Face and construct validity evidences (converging validity analysis and confirmatory factor analysis) were examined as well as reliability, taking into account internal consistency aspects, inter-rater and test-retest stability. The resulting scale showed adequate technical features. The original version, supported by De la Torre’s model, was composed by 12 indicators. This study’s findings maintained 9 of them but, considering new analyses, only 4 of the original ones were retained. This 4-indicator model obtained a better fit to empirical data and good indexes of correlation with a verbal creativity measure, as well as good reliability indicators (internal consistency, inter-rater and test-retest). Findings are discussed taking into account theoretical basis.